Assessing the Effects of POGIL-Based Instruction versus Lecture-Based Instruction on Grade 12 Self-Efficacy and Performance in Circular Motion Unit - Alneyadi, Saif (Journal of Ecohumanism, 2024)
This study investigates the impact of lecture-based instruction and process-oriented guided inquiry learning (POGIL)-based instruction on the self-efficacy and performance of Grade 12 students. The researchers used a quasi-experimental, pretest-posttest design to compare the effects of POGIL-based instruction to lecture-based instruction, as measured by three cognitive outcomes: knowing, applying, and reasoning (KAR)." self-efficacy as measured by physics learning variables", "understanding of physics", and "willingness to learn". The study included 110 participants (54 in the treatment group and 56 in the control group) and was conducted in two government high schools in Alain, one for boys and one for girls. POGIL-based instruction was used to teach a circular motion unit in physics to the treatment group, while lecture-based instruction was used for the control group. The findings show that POGIL-based instruction had a statistically significant positive impact on science performance and self-efficacy when compared to lecture-based instruction. Furthermore, after the intervention, there was a positive correlation between participants' KAR test performance and their self-efficacy toward scientific inquiry. The study recommends a shift toward POGIL-based instruction to improve students' performance and self-efficacy and suggests that future research should include a broader range of schools, teachers, and advisors.